DEVELOPING POP-UP BOOK WITH THE TOPIC OF HOW LIVING THINGS ADAPT TO ENVIRONMENT IN THE FOURTH GRADE OF ELEMENTARY SCHOOL - Ni Komang Indah Yani; I Gede Margunayasa; Ni Nyoman Kusmariyatni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to develop a pop-up book media with the topic of how living things adapt to the environment in the fourth grade of elementary school whose validity had been tested. This research is a development research conducted using ADDIE model which consists of 5 stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. However, in this study the implementation and evaluation stage were not carried out due to limited resources, manpower, costs, and research time. The subject of this research was the pop-up book while the object of this study was the validity of the developed media. The data collection method in this study was a questionnaire. The instrument used to measure the validity of the media was a rating scale in the form of assessment sheet from the experts. The validation data of pop-up book that had been collected was analyzed using the mean formula to find out the average score of the validity of the pop-up book. The average value of the validity score of the pop-up book that has been validated by the experts was 4.90 with very good qualifications. Based on the results, it can be stated that the pop-up book that had been developed were declared as valid and applicable.